Assessment the association between foodborne disease and food safety knowledge and practices among pilgrims during Hajj in Saudi Arabia - Nada Msrahi; Arwa Turkistani (Journal of Health, Population and Nutrition)
Abstract Background The assessment of pilgrims’ knowledge and practices regarding food and water safety during Hajj may contribute to a reduction in foodborne disease (FBD) cases. Thus, the food safety knowledge and practices of consumers during Hajj and its association with FBD and demographic information were investigated in this study. Methods A cross-sectional study was conducted among pilgrims during Hajj 2023. A self-reported questionnaire comprising 4 sections (demographic data, pilgrims’ food safety knowledge and practice, and FBD) was distributed for data collecting. Statistical tests performed including one-way ANOVA, independent samples t-tests, Chi-square, and Pearson’s correlation. Results Out of 409 pilgrims, 58% were females and 41% were males with a mean age of 38.9 years. The overall food safety knowledge level among pilgrims was above-average, while their overall food safety practice level was below-average. Those with higher education and employed had the highest knowledge score. Male and unemployed pilgrims had the highest practice score. FBD symptoms were associated with knowledge and practice (p = 0.002 and 0.0001, respectively). Conclusions The findings confirmed the above-average level of pilgrims’ food safety knowledge. Nevertheless, some risky practices during Hajj were reported. FBD and some factors were significantly associated with food safety knowledge and practices. This study suggests educational interventions to enhance pilgrims’ behaviors and practices towards food before and during Hajj.